2018
DOI: 10.3390/biom8040144
|View full text |Cite
|
Sign up to set email alerts
|

Furanoid F-Acid F6 Uniquely Induces NETosis Compared to C16 and C18 Fatty Acids in Human Neutrophils

Abstract: Various biomolecules induce neutrophil extracellular trap (NET) formation or NETosis. However, the effect of fatty acids on NETosis has not been clearly established. In this study, we focused on the NETosis-inducing ability of several lipid molecules. We extracted the lipid molecules present in Arabian Gulf catfish (Arius bilineatus, Val) skin gel, which has multiple therapeutic activities. Gas chromatography–mass spectrometry (GC-MS) analysis of the lipid fraction-3 from the gel with NETosis-inducing activity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
30
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(34 citation statements)
references
References 51 publications
(106 reference statements)
4
30
0
Order By: Relevance
“…It is generally recognized that NETosis is a unique type of neutrophil death via the NADPH-oxidase (Nox)-dependent pathway [40]. Previous evidence [41] expressed that OA only induces Nox-dependent NETosis in human neutrophils. This explains the enhanced NET formation and cell death by the nanosystems with an OA dose at 10 μg/ml.…”
Section: Discussionmentioning
confidence: 99%
“…It is generally recognized that NETosis is a unique type of neutrophil death via the NADPH-oxidase (Nox)-dependent pathway [40]. Previous evidence [41] expressed that OA only induces Nox-dependent NETosis in human neutrophils. This explains the enhanced NET formation and cell death by the nanosystems with an OA dose at 10 μg/ml.…”
Section: Discussionmentioning
confidence: 99%
“…The production of certain metabolites indicates that inflammation has occurred. Most commonly, inflammation induces neutrophil aggregation and promotes the formation of neutrophil extracellular traps, and furanoid fatty acids induce NADPH oxidase and the production of reactive oxygen species in the mitochondria (Khan et al, 2018). Chemotaxis neutrophils can also secrete leukotriene B4 substances, which increase the recruitment of neutrophils (Majumdar et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Other n-6 PUFAs ↓ T cell activation and ↓ IL-2 and IFN-γ production by EPA-DC stimulated T cells (AA) [58] ↓ Responses to LPS, independent from NF-κB and eicosanoid system [58] Neutrophils ↑ TNFR1 and TNFR2 receptor expression mediated via PKC, ERK1/2 and cPLA 2 (AA) [88] ↓ ATP production and ↑ LDH release [89] ↑ Mitochondria depolarization and lipid accumulation [90] ↑ ROS production dependent from calcium signaling (AA) [86] T cells ↓ T-cell proliferation in DCs and T cell co-culture by ↑ FoxP3 + T cell population (AA) [77] OA Neutrophils ↑ ROS production, phagocytosis and killing capacities, ↑ VEGF, CXCL3 and IL-1β production [91][92][93] ↑ NETosis [94] T cells ↑ Apoptosis via caspase-3 pathway (high doses) [87] PA Macrophages ↑ Activation of TLR4 and NF-κB pathway [95] ↑ IL-18 and TNF-α secretion [96] ↑ Activation of TLR2 and NLRP3 inflammasome and ↑ of IL-1β-secretion [97] Dendritic cells ↑ TLR4 endocytosis, ↑ CD86, and CD83 expression and ↑ TLR4-dependent secretion of IL-1β via NF-κB canonical pathway [98] Dendritic cells ↑ ROS production [98] ↑…”
Section: Cell Typementioning
confidence: 99%
“…Both EPA and DHA increase the generation of ROS and TNF-α, but only DHA can enhance phagocytosis, antifungal properties, and IL-1β secretion by neutrophils [59]. Additionally, Khan et al showed that dietary SFAs and MUFAs can induce NADPH-oxidase-dependent neutrophil extracellular traps formation in human neutrophils in vitro [94]. To explain these contradictory effects of various PUFAs on neutrophil biology, it has been hypothesized that the ratio of n-6/n-3 PUFAs, rather than n-3 PUFAs amounts, is essential to exert anti-inflammatory effects [152].…”
Section: Neutrophilsmentioning
confidence: 99%